Contextual Weather and Climate Broadcast System: Case for Nganyi Community Farmers in Kisumu - Orwa Ochieng, Dr. Daniel; Wanjiru Kamau, Sharon (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Mobile phone ownership has seen a steady increase in Kenya in the last five years and currently stands at 28.08 million mobile phone subscribers spread throughout the country. With poor road infrastructure, the mobile phone has become invaluable in reaching many people and can be useful in broadcasting information such as in education, health, agriculture and many other sectors. Previous survey and analysis indicates that implementation of technology is one of the key effectors of turnaround of rural economies. The main challenge that lies ahead is one of strengthening the innovation capabilities of African in order to be able to successfully address negative impacts caused by climate change and achieve broader economic growth and development.